Enhanced Process Integration and Device Performance of Carbon Nanotubes via Flocculation. Issue 10 (1st August 2018) - Gao, Theodore Z.; Lei, Ting; Molina‐Lopez, Francisco; Bao, Zhenan
Abstract: Polymer sorting is a promising strategy for purifying semiconducting carbon nanotubes (CNTs), offering high selectivity and yield, in addition to low cost and scalability. However, sorting conditions that maximize the yield lead to CNT dispersions with significant amounts of excess sorting polymer. This has undesirable implications for CNT device performance, such as decreased charge carrier mobility and on–off ratio. Here, a method for removing excess sorting polymer based on flocculation is demonstrated. This approach is broadly applicable to various sorting polymers and facilitates recycling of the sorting polymer. In addition, devices made with flocculated CNTs exhibit improved performance and require minimal post‐processing steps. Flocculation was found to be particularly effective for inkjet‐printed CNT transistors on SiO2, producing devices with mobilities ≈10 cm 2 V ‐1 s ‐1 and on–off ratios ≈10 6 . These results show that flocculation is a facile approach to improving the process integration and device performance of polymer‐sorted CNTs. Abstract : Flocculation of polymer‐sorted carbon nanotubes (CNTs) is introduced as a facile method for reducing excess polymer content in CNT dispersions. This approach is applicable to various sorting polymers and eliminates the need for postdeposition polymer removal. Using flocculated CNTs, inkjet‐printed transistors with mobilities ≈10 cm 2 V ‐1 s ‐1 and on–off ratios ≈10 6 are achieved, establishing the efficacy of flocculation for CNT electronics.